Nurses and information a study on the information needs and information-seeking behavior of nurses in connection to their specialization and duration in practice in multiple medical institutions in Metro Manila - Cruz, Johann Sebastian H.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
In order to aid nurses, the information needs, and information-seeking behavior of nurses are supposed to be continuously monitored for changes and differences. Now with the growing variety of nurses and the continuous production of information, it is essential the information needs, and information-seeking behavior of nurses are studied in order to deliver and come up with new plans and strategies to handle them. Unfortunately, the studies on the information needs and information-seeking behavior of nurses have remained scarce in the setting of the Philippines. This study aims to provide this needed information by studying the information needs and Information Seeking behavior of nurses in Metro Manila with respect to their specializations and time spent in practice. This study used questionnaires to gather data from a total of 153 nurses from different hospitals. The findings show the nurses from different specializations and time spent in the practice prioritize searching for specific information over others. The study also found the information-seeking behavior of nurses from different categories have evolved leaning to using Web-based resources.
Thesis
Keywords: Information services; Information behavior; Information needs analysis